Differences in the diagnosis of sweat gland tumors with other histopathologically similar skin tumors - Maylita Sari; Arisia Fadila (Explorer Front, 2022)
Sweat gland tumors are still relatively rare compared to other skin tumors. The clinical features of sweat gland tumors are non-specific and are rarely encountered in daily diagnostic practice. This article aims to explain the features of benign sweat gland tumors based on clinical and histopathological features. Many sweat gland tumors have overlapping clinical features with other tumors, whether from other adnexal tumors or even malignant tumors. Fulton et al. divided eccrine and apocrine gland tumors into six groups based on the similarity of the basic histopathological features, which could help clinicians better establish benign sweat gland tumors. The histopathological examination could complement history taking and physical examination to establish benign sweat gland tumors.